The Approaches of Advanced Industrial Engineering in Next Generation Manufacturing Systems - Micieta, Branislav; Binasova, Vladimira; Haluska, Michal (Communications - Scientific letters of the University of Zilina, 2014)
The article deals with new approaches to the development trends in the advanced industrial engineering in manufacturing systems. The authors emphasize the need for integration of advanced industrial engineering in next generation manufacturing systems, which responds to new trends of production, innovation and advanced technology. This integration represents a sustainable development so that humanization of work is increased, more effective use of natural and energy resources are achieved and production costs are reduced. Trends in the products manufacturing must meet both industrial engineering as well as production management. The development trends in the industrial engineering in manufacturing organizations must use methods and tools of advanced industrial engineering to achieve competitiveness. The third part of this article deals with specification of these approaches in next generation manufacturing systems.